Circuit design techniques for Power Efficient Microscale Energy Harvesting Systems - Eltaliawy, Ayman Abdelaziz (AUC Knowledge Fountain, 2014)
Power Management is considered one of the hot topics nowadays, as it is already known that all integrated circuits need a stable supply with low noise, a constant voltage level across time, and the ability to supply large range of loads. Normal batteries do not provide those specifications. A new concept of energy management called energy harvesting is introduced here. Energy harvesting means collecting power from ambient resources like solar power, Radio Frequency (RF) power, energy from motion...etc. The Energy is collected by means of a transducer that directly converts this energy into electrical energy that can be managed by design to supply different loads. Harvested energy management is critical because normal batteries have to be replaced with energy harvesting modules with power management, in order to make integrated circuits fully autonomous; this leads to a decrease in maintenance costs and increases the life time. This work covers the design of an energy harvesting system focusing on micro-scale solar energy harvesting with power management. The target application of this study is a Wireless Sensor Node/Network (WSN) because its applications are very wide and power management in it is a big issue, as it is very hard to replace the battery of a WSN after deployment. The contribution of this work is mainly shown on two different scopes. The first scope is to propose a new tracking technique and to verify on the system level. The second scope is to propose a new optimized architecture for switched capacitor based power converters. At last, some future recommendations are proposed for this work to be more robust and reliable so that it can be transfered to the production phase. The proposed system design is based on the sub-threshold operation. This design approach decreases the amount of power consumed in the control circuit. It can efficiently harvest the maximum power possible from the photo-voltaic cell and transfer this power to the super-capacitor side with high efficiency. It shows a better performance compared to the literature work. The proposed architecture of the charge pump is more efficient in terms of power capability and knee frequency over the basic linear charge pump topology. Comparison with recent topologies are discussed and shows the robustness of the proposed technique.